Inter-Provincial Dialogue On “The Innovation Model for Integrated Decentralized Food System Governance at the District Level” in Cambodia’s Mekong Delta - Sok, Sao; Kong, Heng (WorldFish, 2024)
A one-day inter-provincial dialogue workshop titled "The Innovation Model for Integrated Decentralized Food System Governance at the District Level" was held in Cambodia’s Mekong Delta with 60 participants (10 females) from various government agencies, research institutions, and development organizations. The workshop included representatives from provincial governors, district authorities, fisheries and agricultural departments, environmental agencies, and international organizations like WorldFish, IRRI, and IIRR. The event utilized interactive presentations and group discussions, featuring six presentations and two discussion sessions. Participants gained insights into the innovation model aimed at promoting decentralized, integrated, and inclusive food systems. Discussions highlighted the importance of collaboration between government agencies, donors, and stakeholders to broaden the model’s adoption.